FEMININE EPISTEMOLOGY WITHIN ACADEMY: An Alternative Way of Pedagogical Practice - Naznin (Journal of Dharma, 2016)
The role of women in the field of teaching has been undervalued and denigrated for a long time by educational experts. Though the preponderance of women in teaching enabled them to apply their distinct ways of learning and teaching to the profession effectively, they were not recognized either in the historical texts of education or in the philosophy of education. The study analyses the traditional teaching patterns that persist and dominate contemporary pedagogical practice. Accordingly, women teachers are coerced to adopt a 'masculine' pedagogy, neglecting unique feminine qualities and abilities in education. Ensuing traditional patterns not only deprive women from exhibiting their inherent abilities but also impede positive changes in the quality of teaching. It is argued that the experience of mothering in the private sphere offers alternative ways of remodelling the pedagogical practices, facilitating professional educators in developing gender sensitivity, and sensitivity to different learning abilities among students.